Synergistic effects of TiO2 photocatalysis in combination with Fenton-like reactions on oxidation of organic compounds at circumneutral pH - Kim, Hyung-Eun; Lee, Jaesang; Lee, Hongshin; Lee, Changha (ELSEVIER SCIENCE BV, 2012)
The integration of two different AOPs often offers synergistic reaction routes for the production of (OH)-O-center dot. In this study, synergistic production of (OH)-O-center dot was observed in the combined system of TiO2 photocatalysis and the Fenton-like reaction, causing a drastic enhancement in the oxidation of organic compounds at circumneutral pH values. The photolytic experiments using organic substrates (i.e., phenol, benzoic acid, and methanol) and valence band hole and (OH)-O-center dot scavengers (i.e., formate and tert-butyl alcohol) show that the synergistic effects result from dual roles of iron as an electron acceptor to facilitate charge separation in TiO2 photocatalyst and as a Fenton reagent to catalyze conversion of H2O2 into (OH)-O-center dot. A noteworthy observation is that the adsorption of iron onto the photoexcited TiO2 surface possibly modifies electron transfer properties of iron toward H2O2 at neutral pH to convert the resultant reactive oxidant from Fe(IV) into a stronger form, likely (OH)-O-center dot. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ZERO-VALENT IRON; POLYOXOMETALATE-ENHANCED OXIDATION; HYDROGEN-PEROXIDE; FERROUS ION; OXYGEN; DEGRADATION; WATER; SEMICONDUCTOR; RADICALS; OXIDANTS